Application of visible light on copper-doped titanium dioxide catalyzing degradation of chlorophenols - Justin Chun Te Lin (2018)
© 2017 Elsevier B.V. Chlorophenols are extensively used in the anthroposphere, and their fates in the atmosphere, hydrosphere, biosphere and lithosphere and their degradations under natural light of great interests. The homogeneous photocatalytic degradation of 2-chlorophenol (2-CP) in titanium dioxide suspensions containing copper ions or/and sulfates has been well examined. In this study, TiO 2 is directly doped with copper sulfate by a sol-gel method to promote its visible light activity (VLA) following a post-calcination step. The effects of three parameters of synthesis (calcination temperature, amounts of dopant and nitric acid) on 2-CP degradations were experimentally investigated using a three-factor, two-level factorial design in the first stage. Catalysts of the most significant synthetic parameters were further synthesized at five calcined temperatures and characterized in the second stage. 2-CP was completely removed using catalysts that were doped 0.21 mol.% CuSO 4 with 0.1 vol.% nitric acid and then calcined at 300 °C for 6 h. Morphological variations with doping amount are observed from scanning electron micrographs. XRD patterns demonstrated a transformation from amorphous to the anatase phase, with replacement of Ti 4+ by Cu 2+ in the crystal structure of TiO 2 . UV–visible light diffuse reflectance spectra of the doped catalysts exhibited red-shifts, revealing their VLA. Surface areas, measured by the BET method, decreased as the calcination temperatures increased, and the pore sizes increased. Moreover, effect of three operational parameters, including: (del) initial concentration of 2-CP, initial pH and the photocatalyst dosage, under visible-light irradiation were investigated to simulate the scenarios of degradation in the natural and artificial conditions. Optimal operational parameters were obtained at a catalyst dosage of 3 g·dm −3 , an initial 2-CP concentration of 20 ppm and a solution pH of 5.5. The pH zpc of the undoped and CuSO 4 -doped TiO 2 were determined to be 3.5 and 3.84.